A soft-linking method for responsive modelling of decarbonisation scenario costs - Cameron, Ché; Foley, Aoife; Lund, Henrik; McLoone, Seán (International Journal of Sustainable Energy Planning and Management, 2024)
This study presents a methodology that integrates EnergyPLAN and Quintel Energy Transition Model (ETM). Quintel ETM encompasses a holistic view of energy demand and supply from a fixed base year and its user interface enables unparalleled public engagement, but it is constrained by its limited flexibility in updating deeply embedded cost parameters. This shortcoming becomes critical when considering the rapid pace of technological change and market volatility which is characteristic of contemporary energy systems. EnergyPLAN, with its focus on detailed, customizable cost analysis in heating and power sectors, compensates for these limitations by offering a user-friendly interface and a track record of validated costing approaches. This work contributes the `epnlink` python library for EnergyPLAN – a flexible input-output parser with functionality that extends beyond this study. A soft-linking methodology to map ETM outputs to EnergyPLAN inputs is developed and demonstrated on a case study of Northern Ireland. Alternative pathways to net zero carbon by 2050 are explored, where infrastructure for power and non-industrial heat, and total fuel usage are costed. The demonstrated pipeline has broad applicability as a template to enhance the agility and precision of key cost projections for responsive and strategic energy planning across diverse geographical contexts.